2020
DOI: 10.2196/21367
|View full text |Cite
|
Sign up to set email alerts
|

Health Outcomes from Home Hospitalization: Multisource Predictive Modeling

Abstract: Background Home hospitalization is widely accepted as a cost-effective alternative to conventional hospitalization for selected patients. A recent analysis of the home hospitalization and early discharge (HH/ED) program at Hospital Clínic de Barcelona over a 10-year period demonstrated high levels of acceptance by patients and professionals, as well as health value-based generation at the provider and health-system levels. However, health risk assessment was identified as an unmet need with the pot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…In line with the existing literature, home hospitalization and territorial medicine are positively related to efficiency in both models [ 60 ]. Both are measures to strengthen peripheral units, that are endowed with a high degree of autonomy.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In line with the existing literature, home hospitalization and territorial medicine are positively related to efficiency in both models [ 60 ]. Both are measures to strengthen peripheral units, that are endowed with a high degree of autonomy.…”
Section: Discussionsupporting
confidence: 83%
“…Home hospitalization is a cost-effective alternative to conventional hospitalization for selected patients. In addition, some studies have shown a positive impact on quality of care, and patient satisfaction [ 60 ]. It is measured here as the percentage of special units established in relation to those expected for the population.…”
Section: Methodsmentioning
confidence: 99%
“…In our center, a tertiary university hospital providing specialized care to a catchment population of 520,000 citizens, HaH was implemented in 2006 as a mainstream service across specialties covering two modalities of HaH: hospital avoidance (HaH-HA) and early discharge (HaH-ED) [7,15,16]. The service provides acute, home-based, short-term care aiming at either entirely replacing conventional hospitalization (hospital avoidance) or accelerating discharge (early discharge).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, multisource clinical predictive modeling approaches, considering various determinants of health (eg, clinical, social, populational, lifestyle), have become an effective strategy for subject-specific risk assessment to prevent morbidity-related adverse events leading to hospital readmissions [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%